2021
DOI: 10.1073/pnas.2025601118
|View full text |Cite
|
Sign up to set email alerts
|

Host barriers to SARS-CoV-2 demonstrated by ferrets in a high-exposure domestic setting

Abstract: Ferrets (Mustela putorius furo) are mustelids of special relevance to laboratory studies of respiratory viruses and have been shown to be susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and onward transmission. Here, we report the results of a natural experiment where 29 ferrets in one home had prolonged, direct contact and constant environmental exposure to two humans with symptomatic disease, one of whom was confirmed positive for SARS-CoV-2. We observed no evidence of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 52 publications
2
23
0
1
Order By: Relevance
“…Insofar as data limitations preclude perfect computational predictions of zoonotic capacity (e.g., limited ACE2 sequences, crystal structures, or species trait data), laboratory experiments are also limited in assessing true zoonotic capacity. For SARS-CoV-2 and other host-pathogen systems, animals that are readily infected in the lab appear to be less susceptible in non-lab settings (ferrets in the lab vs. mixed results in ferrets as pets [36,53,141]; rabbits in the lab vs. rabbits as pets [48,142]. Moreover, wildlife hosts confirmed to shed multiple zoonotic viruses in natural settings (e.g., bats, [143]) can be much less tractable for whole-animal laboratory investigations (for instance, requiring high biosecurity containment and very limited sample sizes in unnatural settings).…”
Section: Discussionmentioning
confidence: 99%
“…Insofar as data limitations preclude perfect computational predictions of zoonotic capacity (e.g., limited ACE2 sequences, crystal structures, or species trait data), laboratory experiments are also limited in assessing true zoonotic capacity. For SARS-CoV-2 and other host-pathogen systems, animals that are readily infected in the lab appear to be less susceptible in non-lab settings (ferrets in the lab vs. mixed results in ferrets as pets [36,53,141]; rabbits in the lab vs. rabbits as pets [48,142]. Moreover, wildlife hosts confirmed to shed multiple zoonotic viruses in natural settings (e.g., bats, [143]) can be much less tractable for whole-animal laboratory investigations (for instance, requiring high biosecurity containment and very limited sample sizes in unnatural settings).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of households with ferrets is low compared to households with cats and dogs, and ferrets are rarely kept in large groups, in contrast to mink which are held on commercial fur farms. Interestingly, a recent study outlined a case in which two symptomatic COVID-19-positive individuals were in close and prolonged contact with 29 free-roaming pet ferrets, providing ample opportunity for natural transmission [ 173 ]. However, clinical samples failed to provide evidence of active ferret infection or seroconversion in this instance.…”
Section: Main Textmentioning
confidence: 99%
“…It is conceivable that after transmission from humans to minks, the virus evolved further in mink to adapt to the new host, with efficient binding of SARS-CoV-2 S protein to mink ACE2 a prerequisite for ready transmission among minks. Of interest, a recent study reported the absence of natural SARS-CoV-2 human-to ferret transmission in a high-exposure setting, and genetic analysis suggested that infection of ferrets may require viral adaptation 32 . Here we demonstrate that the emergence of Y453F in SARS-CoV-2 spike significantly enhanced its interaction with other Mustela ACE2 orthologs—namely ferret and stoat—conferring a potential fitness advantage in Mustela species that could subsequently promote virus transmission and possible risk of animal-adapted virus with genetic alterations to spilling over into humans.…”
Section: Discussionmentioning
confidence: 99%